Map navigation for mobile tourist / Rohana Abd Jalil - Abd Jalil, Rohana (2007)
Recent years have seen rapid growth in the area of map-based mobile application system for tourist information services. Current map-based application for tourist used Global Positioning System (GPS) technologies that make it possible to track user movements and determine a user's current location. However, using this technology have some restricted because of the limited capabilities which it can not work properly inside buildings or in narrow path and light-based systems such as infrared beacon require a tight infrastructure. Therefore, there is a need for a development of this system where map navigation mobile tourist guides should be able to cope with positional information of varying quality. This system is used an rule base algorithm to get an output. The result of this system is come out with the prototype system that adapts the rule base algorithm. Because of some constraint, so this system is not exploring more on the development of algorithm and representation of map. Future work may be can used a digital map on map representation and other technique on searching algorithm.